Psychiatric Morbidity Pattern in a Child and Adolescent Guidance Clinic - Tulachan, P; Chapagain, M; Kunwar, AR; Sharma, VD (Journal of Psychiatrists’ Association of Nepal, 2014)
DOI: http://dx.doi.org/10.3126/jpan.v1i1.9923 Journal of Psychiatrists' Association of Nepal Vol.1(1) 2011: 20-23